Lucas Numbers Which Are Concatenations of Two Repdigits - Yunyun Qu; Jiwen Zeng (Mathematics, 2020)
In this paper, we find all Lucas numbers written in the form <semantics><mover>c⋯cd⋯d¯</mover></semantics>, where <semantics><mover>c⋯cd⋯d¯</mover></semantics> is the concatenation of two repdigits in base 10 with <semantics>c,d∈{0,1,⋯,9}</semantics>, <semantics>c≠d</semantics> and <semantics>c>0</semantics>.